Levetiracetam alleviates cognitive decline in Alzheimer’s disease animal model by ameliorating the dysfunction of the neuronal network - Zheng, Xiang-Yu; Zhang, Hai-Chen; Lv, Yu-Dan; Jin, Feng-Yan; Wu, Xiu-Juan; Zhu, Jie; Ruan, Yang (Frontiers in Aging Neuroscience, 2022)
Background: Patients with Alzheimer’s disease (AD) have a significantly higher risk of seizures than other individuals in an age-matched population, suggesting a close association between epilepsy and AD. We aimed to examine the effects of levetiracetam (LEV)—a drug for treating seizures—on learning and memory and the neuropathological features of AD. Methods: We crossbred APP23 mice with MAPT transgenic mice to generate APP23/MAPT mice. These mice were treated with different concentrations of LEV in the presence of kainic acid (KA) for 3 months. Results: Low doses of LEV alleviated the effects of KA on memory defects in APP23/MAPT mice. Mechanistic investigations showed that low concentrations of LEV decreased tau phosphorylation by reducing the activities of cyclin-dependent kinase 5 and glycogen synthase kinase 3α/β, thus rescuing neurons from synaptic dystrophy and apoptosis. Low doses of LEV inhibited the effects of KA (i.e., inducing neuroinflammation and impairing the autophagy of amyloid β-peptide), thus improving cognitive decline. High concentrations of LEV decreased the production and deposition of amyloid β-peptide (Aβ) by reducing the expression of β-site APP-cleaving enzyme 1 and presenilin 1. However, high concentrations of LEV also induced neuronal apoptosis, decreased movement ability in mice, and did not alleviate cognitive decline in AD mice. Conclusions: Our results support the hypothesis that aberrant network activity contributes to the synaptic and cognitive deficits in APP23/MAPT mice. A low concentration of LEV may help ameliorate abnormalities of AD; however, a high LEV concentration did not induce similar results.